PENGEMBANGAN RUBRIK PERFORMANCE ASSESSMENT PADA PRAKTIKUM HIDROLISIS GARAM - Puspitasari, Nila; Haryani, Sri; Widiarti, Nuni (Jurusan Kimia, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Semarang, 2014)
This research aims to produce innovation of performance assessment rubric on practicum salt hydrolysis material. The rubric was being consulted and validated by experts, then it was being revised and tested. The trial result was being analyzed and revised, then usage test was given. The research was conducted at SMA in Semarang using purposive sampling technique. A small scale was given to ten students and large scales were given to the students in class XI IPA 3 and XI IPA 4. The results showed that the validity of innovation of performance assessment rubric by experts was 86.46%. Implementation innovation of performance assessment rubric on practicum salt hydrolysis